Environmental education : an approach to sustainable development = L'éducation environnementale : approches pour un développement durable - Schneider, Hartmut; Vinke, Jacoline; Weekes-Vagliani, Winifred; Organisation for Economic Co-operation and Development. Development Centre (Organisation for Economic Co-operation and Development, 1993)
Conclusion (s. 241-246). - Conclusion (s. 249-253).
Keywords: kehitysmaat; kestävä kehitys; koulutus; ympäristökasvatus